Pengaruh Penerapan Standar Akuntansi Pemerintah, Sistem Pengendalian Internal dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pada Organisasi Pemerintah Daerah Provinsi Jambi Dengan Komitmen Organisasi Sebagai Variabel Moderating - Luthfya, Ade; Rahayu, Sri; Friyani, Rita (Jurnal Akuntansi & Keuangan Unja, 2024)
Accounting has now increasingly developed in the era of globalisation, especially financial reporting which is very important. The purpose of this study was to test and obtain empirical evidence on the Effect of Implementation of Government Accounting Standards, Internal Control Systems and Utilization of Information Technology on the Quality of Financial Statements in Jambi Province Local Government Organisations with Organisational Commitment as a Moderating Variable. The research sample used Purposive Sampling technique. The quantitative method used as an analytical approach has a manifestation to test and verify a theory, positioning the theory deductively to become a benchmark for determining and solving a problem in research. The subjects of this study were Regional Apparatus Organisations located in Jambi Province. Sampling of employees related to the preparation of financial reports, data collection by distributing questionnaires with the number of respondents was 93 people. The results of this study found that the application of government accounting standards and the use of information technology had an effect on the quality of financial reports, while the internal control system had no effect. Organisational commitment is able to moderate the influence between the internal control system and the use of technology on the quality of financial statements, while organisational commitment is not able to moderate the influence between government accounting standards on the quality of financial statements.